Assess the Effectiveness of “First Aid Training Program” in Terms of Knowledge and Skills Among School Teachers of Selected Schools of Ambala, Haryana”: A Quasi Experimental Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: As the incidence of medical emergencies is rising, the demand of the knowledgeable andskilled personnel is also needed. It is important for every person to be competent enough to tackle all theemergency situations anywhere. First aid training helps to make a person able to give actual immediate careand safety awareness. The objective of the study is to assess the effectiveness of first aid training program interm of knowledge and skill among school teachers.Methodology: A Quasi-Experimental study following one pre-test post-test design was used. Participant’sdata was collected from 105 school teachers from 12 schools (9 govt. and 3 private) using Total enumerativesampling and the schools were conveniently selected. Knowledge and skills were assessed by using structuredknowledge questionnaire and observational checklist respectively.Conclusion: Data was analyzed using SPSS 16. The t test analysis showed a significant difference beforeand after the administration of first aid training program in term of knowledge(t=37.05 and p= 0.001)andskills (t=84.485 and p=0.000) at 0.05 level of significance. There was significant association of pre-testknowledge scores with educational status of school teachers.
Keywords: effectiveness, First Aid Training Program, knowledge, skills, school teachers.